2017
DOI: 10.1002/bies.201600200
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs at the epicenter of intestinal homeostasis

Abstract: Maintaining intestinal homeostasis is a key prerequisite for a healthy gut. Recent evidence points out that microRNAs (miRNAs) act at the epicenter of the signaling networks regulating this process. The fine balance in the interaction between gut microbiota, intestinal epithelial cells, and the host immune system is achieved by constant transmission of signals and their precise regulation. Gut microbes extensively communicate with the host immune system and modulate host gene expression. On the other hand, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 118 publications
0
23
0
1
Order By: Relevance
“…Another layer of regulatory complexity consists of post-transcriptional regulation involving microRNA (miRNA)–messenger RNA (mRNA) target interactions. In addition to specific miRNAs associated with intestinal homeostasis and permeability [ 14 17 ], miRNA–mRNA interactions result in competing-endogenous RNA (ceRNA) function. miRNAs may target multiple RNA transcripts, while an mRNA transcript may be targeted by multiple miRNAs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Another layer of regulatory complexity consists of post-transcriptional regulation involving microRNA (miRNA)–messenger RNA (mRNA) target interactions. In addition to specific miRNAs associated with intestinal homeostasis and permeability [ 14 17 ], miRNA–mRNA interactions result in competing-endogenous RNA (ceRNA) function. miRNAs may target multiple RNA transcripts, while an mRNA transcript may be targeted by multiple miRNAs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as a prototypical HDACi, butyrate regulates the expression of many protein‐coding genes and also alters miRNA expression in many solid and nonsolid cancer cell lines as well as in the intestines. For instance, butyrate downregulates the expression of oncogenic miRNAs (miRs) (miR‐17‐92, miR‐106b‐25, and miR‐106a‐363 clusters) and upregulates the expression of miRNA suppressors (miR‐15a and miR‐16) (for review see Ali et al and Belcheva).…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimmentioning
confidence: 99%
“…It has been found that microbiota-produced butyrate regulated hepatic cell apoptosis and proliferation by inducing miR-22 expression ( Pant et al, 2017 ). The research about gut microbiota–miRNA interaction has revealed that the gut microbiota could be regulated by host-secreted miRNAs and the gut microbiota may affect the host via inducing miRNAs ( Liu et al, 2016 ; Belcheva, 2017 ). The gut microbiota–miRNAs-diseases axis could serve as a new direction for future investigation.…”
Section: Introductionmentioning
confidence: 99%